Análise do hiperconsumo de produtos importados entre diferentes gerações - Silva, Douglas Gomes da (My University, 2025)
This study aimed to analyze the hyperconsumption behavior of imported products among consumers from Generation Y (Millennials) and Generation Z, identifying the main differences between these groups. The research investigated the frequency of imported product consumption, the motivational factors driving this behavior, perceptions of status, quality, and exclusivity associated with imported products, as well as the degree of influence of social media and digital marketing. Additionally, it examined consumers' awareness of the impacts of excessive consumption. The study adopted a quantitative, descriptive, and comparative approach, using a structured questionnaire as the data collection instrument. The sample consisted of individuals from Generation Y (up to 30 years old) and Generation Z (minimum age of 18), residing in Brazil and regularly purchasing imported products. The results revealed significant differences between Generations Y and Z regarding consumption patterns, motivations, and the influence of social media. The data indicated that the perceived quality of imported products is the main motivating factor for consumption in both generations, with this perception being more pronounced among Generation Z. This generation also exhibited a higher consumption rate, especially in clothing and accessories, and attributed greater symbolic value to imported products in relation to the construction of social image. Both generations demonstrated frequent use of social media, particularly in following international brands. However, engagement with global trends and foreign brands was more evident among individuals from Generation Z.In the field of communication, it was found that advertising campaigns disseminated through social media generate greater acceptance and impact among the generations analyzed, in comparison to traditional media advertising, whose effectiveness proved to be lower.This study contributes to a better understanding of generational dynamics in consumer behavior, offering insights for more targeted marketing strategies and reflections on conscious consumption. [resumo fornecido pelo autor]
O presente trabalho teve como objetivo analisar o comportamento de hiperconsumo de produtos importados entre consumidores das gerações Y (Millennials) e Z, identificando as principais diferenças entre esses grupos. A pesquisa investigou a frequência de consumo de produtos importados, os fatores motivacionais que impulsionam esse comportamento, a percepção de status, qualidade e exclusividade associada aos produtos importados, bem como o grau de influência das redes sociais e do marketing digital. Além disso, analisou-se o nível de consciência dos consumidores sobre os impactos do consumo excessivo. O estudo adotou uma abordagem quantitativa, de caráter descritivo e comparativo, utilizando um questionário estruturado como instrumento de coleta de dados. A amostra foi composta por indivíduos das gerações Y (com até 30 anos) e Z (com idade mínima de 18 anos), residentes no Brasil e com hábito de consumir produtos importados. Os resultados revelaram diferenças significativas entre as gerações Y e Z quanto aos padrões de consumo, motivações e influência das redes sociais. Os dados indicaram que a percepção de qualidade dos produtos importados é o principal fator motivador para o consumo em ambas as gerações, sendo essa percepção mais acentuada na Geração Z. Essa geração também apresentou maior índice de consumo, especialmente de roupas e acessórios, além de atribuir maior valor simbólico aos produtos importados no que se refere à construção da imagem social. Ambas as gerações demonstraram uso frequente das redes sociais, com destaque para o acompanhamento de marcas internacionais. No entanto, o engajamento com tendências globais e com marcas estrangeiras foi mais expressivo entre os indivíduos da Geração Z. No campo da comunicação, constatou-se que campanhas publicitárias veiculadas em redes sociais geram maior aceitação e impacto junto às gerações analisadas, em comparação à publicidade tradicional, cuja eficácia se mostrou reduzida. O estudo contribui para a compreensão das dinâmicas geracionais no comportamento de consumo, oferecendo subsídios para estratégias de marketing mais segmentadas e para reflexões sobre consumo consciente. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Consumo (Economia); Gerações; Comportamento do consumidor; Comércio eletrônico; Produtos importados